Bridging Green Banking Disclosure and Board Effectiveness in Enhancing Corporate Value: Institutional Ownership as a Strategic Moderator in Emerging Markets - Helen Nur Qodaria; Wulan Rahmawati (Dinasti Publisher, 2025)
This study aims to examine the effect of green banking disclosure and board effectiveness on firm value with institutional ownership as a moderating variable. A quantitative approach is employed using secondary data from 42 banking companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023 which consistently published financial and sustainability reports. Data analysis methods include descriptive statistics and regression analysis conducted using Stata MP 17.0 software. The findings reveal that green banking disclosure has a negative and significant effect on firm value, board effectiveness does not have a significant impact on firm value, institutional ownership positively moderates the relationship between green banking disclosure and firm value and the interaction between board effectiveness and institutional ownership does not significantly affect firm value. These results suggest that green banking disclosure should be accompanied by measurable sustainability achievements and well crafted communication strategies to prevent negative market perceptions. The insignificant effect of board effectiveness indicates a need to strengthen the quality of board oversight. Moreover, institutional ownership plays a vital governance role, reinforcing the positive impact of green banking disclosure on firm value.